Repositório personalizado ao candidato para concursos públicos: aplicando métodos efetivos para construção do conhecimento - Silva, Mislene Dalila da (2021)
The thesis was the development of a customized repository for the candidate for public tenders. Therefore, the general objective was to develop a personalized and adaptive environment for students in preparatory courses for public exams, so that they learn according to the level of ability they have, consolidating knowledge in memorization intervals through the Effective Exponential Memorization Method in Binary Base (MMEEBB). In order to maximize student learning capacity and mitigate hidden variables in relation to their development. The content made available to the student will be classified by a specialist professor in the discipline, in order to indicate the best study material. The student can manage their study schedule according to the contest data concurrently with the MMEEBB to follow the reinforcement of the learning interval. Thus, the work is structured in bibliographic, field, exploratory and descriptive research, in which information regarding recommendation systems, competitions, assessments, learning and Structured Knowledge Map (MCE) and MMEEBB methods are collected.